Detection of X‐Rays by Solution‐Processed Cesium‐Containing Mixed Triple Cation Perovskite Thin Films. (18th June 2019) - Basiricò, Laura; Senanayak, Satyaprasad P.; Ciavatti, Andrea; Abdi‐Jalebi, Mojtaba; Fraboni, Beatrice; Sirringhaus, Henning
Abstract: Materials and technology development for designing innovative and efficient X‐ray radiation detectors is of utmost importance for a wide range of applications ranging from security to medical imaging. Here, highly sensitive direct X‐ray detectors based on novel cesium (Cs)‐based triple cation mixed halide perovskite thin films are reported. Despite being in a thin film form, the devices exhibit a remarkably high X‐ray sensitivity of (3.7 ± 0.1) µC Gy −1 cm −2 under short‐circuit conditions. At a small reverse bias of 0.4 V, the sensitivity further increases by orders of magnitude reaching a record value of (97 ± 1) µC Gy −1 cm −2 which surpasses state‐of‐the‐art inorganic large‐area detectors (a‐Se and poly‐CZT). Based on detailed structural, electrical, and spectroscopic investigations, the exceptional sensitivity of the triple cation Cs perovskite is attributed to its high ambipolar mobility‐lifetime product as well as to the formation of a pure stable perovskite phase with a low degree of energetic disorder, due to an efficient solution‐based alloying of individual n‐ and p‐type perovskite semiconductors. Abstract : Direct X‐ray detectors based on cesium‐based triple cation mixed halide perovskite thin films exhibiting a high sensitivity is presented. The high sensitivity is ascribed to a high ambipolar mobility‐lifetime product and to a pure stable perovskite phase with a low degree of energetic disorder.